GLP-1 receptor agonist improves metabolic disease in a pre-clinical model of lipodystrophy - Roumane, Ahlima; Mcilroy, George D.; Sommer, Nadine; Han, Weiping; Heisler, Lora K.; Rochford, Justin J. (Frontiers in Endocrinology, 2024)
Aims: Individuals with lipodystrophies typically suffer from metabolic disease linked to adipose tissue dysfunction including lipoatrophic diabetes. In the most severe forms of lipodystrophy, congenital generalised lipodystrophy, adipose tissue may be almost entirely absent. Better therapies for affected individuals are urgently needed. Here we performed the first detailed investigation of the effects of a glucagon like peptide-1 receptor (GLP-1R) agonist in lipoatrophic diabetes, using mice with generalised lipodystrophy.Methods: Lipodystrophic insulin resistant and glucose intolerant seipin knockout mice were treated with the GLP-1R agonist liraglutide either acutely preceding analyses of insulin and glucose tolerance or chronically prior to metabolic phenotyping and ex vivo studies.Results: Acute liraglutide treatment significantly improved insulin, glucose and pyruvate tolerance. Once daily injection of seipin knockout mice with liraglutide for 14 days led to significant improvements in hepatomegaly associated with steatosis and reduced markers of liver fibrosis. Moreover, liraglutide enhanced insulin secretion in response to glucose challenge with concomitantly improved glucose control.Conclusions: GLP-1R agonist liraglutide significantly improved lipoatrophic diabetes and hepatic steatosis in mice with generalised lipodystrophy. This provides important insights regarding the benefits of GLP-1R agonists for treating lipodystrophy, informing more widespread use to improve the health of individuals with this condition.